Omnidirectional image sensing for automated guided vehicle - Swanepoel, Petrus Johannes (Bloemfontein : Central University of Technology, Free State, 2009)
Automated Guided Vehicles (AGVs) have many different design specifications, although they all have certain design features in common, for instance they are designed to follow predetermined paths, and they need to be aware of their surroundings and changes to their surroundings. They are designed to house sensors for navigation and obstacle avoidance. In this study an AGV platform was developed by modifying an electric wheelchair. A serial port interface was developed between a computer and the control unit of the electric wheelchair, which enables the computer to control the movements of the platform. Different sensors were investigated to determine which would be best suited and most effective to avoid collisions. The sensors chosen were mounted on the AGV and a programme was developed to enable the sensors to assist in avoiding obstacles. An imaging device as an additional sensor system for the AGV was investigated. The image produced by a camera and dome mirror was processed into a panoramic image representing an entire 360o view of the AGV‟s surroundings. The reason for this part of the research was to enable the user to make corrections to the AGV‟s path if it became stuck along the track it was following. The entire system was also made completely wireless to improve the flexibility of the AGV‟s applications.
Thesis (M. Tech.) -- Central University of Technology, Free State, 2009
Keywords: Central University of Technology, Free State - Dissertations; Robots - Control systems; Robots - Programming; Robots - Motion; Remote sensing - Data processing; Dissertations, academic - South Africa - Bloemfontein